Genome mining, in silico validation and phase selection of a novel aldo-keto reductase from Candida glabrata for biotransformation. Issue 1 (1st January 2018) - Basak, Souvik; Sahoo, Nanda Gopal; Pavanasam, Angayar K.
ABSTRACT: Previously, we published cloning, overexpression, characterization and subsequent exploitation of a carbonyl reductase ( cr ) gene, belonging to general family aldo-keto reductase from Candida glabrata CBS138 to convert keto ester (COBE) to a chiral alcohol (ethyl-4-chloro-3-hydroxybutanoate or CHBE). Exploiting global transcription factor CRP, rDNA and transporter engineering, we have improved batch production of CHBE by trinomial bioengineering. Herein, we present the exploration of cr gene in Candida glabrata CBS138 through genome mining approach, in silico validation of its activity and selection of its biocatalytic phase. For exploration of the gene under investigation, 3 template genes were chosen namely Saccharomyces cerevisae YDR541c, YGL157w and YOL151w. The CR showed significant homology match, overlapping of substrate binding site and NADPH binding site with the template proteins. The binding affinity of COBE toward CR (−4.6 Kcal/ mol) was found higher than that of the template proteins (−3.5 to −4.5 Kcal/ mol). Biphasic biocatalysis with cofactor regeneration improved product titer 4∼5 times better than monophasic biotransformation. Currently we are working on DNA Shuffling as a next level of strain engineering and we demonstrate this approach herein as a future strategy of biochemical engineering.